2022
DOI: 10.1007/s11071-022-07444-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of antisymmetric nonlinear damping with application to energy harvesting and vibration isolation under general inputs

Abstract: Beneficial effects of nonlinear damping on energy harvesting and vibration isolation under harmonic inputs have been investigated showing that the introduction of nonlinear damping can increase the harvested energy and reduce the vibration over both the resonant and higher frequency ranges. However, the scenario becomes more complicated when the loading inputs are of more general form such as multi-tone and random inputs, which can produce system responses that are induced by an interaction of system input com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It should also be emphasized that the discussed phenomena can be used in creating a new type of non-reflecting boundary elements without viscous dissipation [45], compared with more traditional elastic-viscous elements [46,47] used for non-reflecting boundaries. Another area for possible application resides in the development of seismic barriers [48,49] used for protection from Rayleigh and Rayleigh-Lamb seismic waves, along with various applications in vibration protection [50][51][52][53][54][55][56]. Actually, the analyzed non-linear elastic media modeled by the Mooney-Rivlin equation of state and exhibiting the mechanical energy dissipation at the acoustic wave propagation open up a new approach in creating seismic and vibration isolation devices.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be emphasized that the discussed phenomena can be used in creating a new type of non-reflecting boundary elements without viscous dissipation [45], compared with more traditional elastic-viscous elements [46,47] used for non-reflecting boundaries. Another area for possible application resides in the development of seismic barriers [48,49] used for protection from Rayleigh and Rayleigh-Lamb seismic waves, along with various applications in vibration protection [50][51][52][53][54][55][56]. Actually, the analyzed non-linear elastic media modeled by the Mooney-Rivlin equation of state and exhibiting the mechanical energy dissipation at the acoustic wave propagation open up a new approach in creating seismic and vibration isolation devices.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the piecewise nonlinear stiffness behaviour, developed due to the interactions of the moving magnet's flux on the coil, facilitated the response of the system in a wider frequency range, enabling it to generate more electrical energy. Similarly, system damping characteristics have been employed in optimising the energy harvested by vibration energy harvesters [16][17][18][19][20][21][22][23][24]. In [16], the authors presented an unconventional way of achieving a tuneable resonant frequency (from high frequency to ultralow frequency) and extending both the bandwidth and peak of the energy harvested, simultaneously, by utilising a distinct structurally supported displacement-dependent nonlinear damping property.…”
Section: Introductionmentioning
confidence: 99%
“…17 Zhu et al 18 proposed and developed a new concept known as the Generalized Associated Linear Equations (GALEs), which can significantly facilitate the nonlinear system analyses and deal with associated practical applications. Recently, Zhu and Lang 19 demonstrated the beneficial effects of the cubic nonlinear damping that is extended to the systems subject to general inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhu and Lang 19 demonstrated the beneficial effects of the cubic nonlinear damping that is extended to the systems subject to general inputs.…”
Section: Introductionmentioning
confidence: 99%